EFEKTIFITAS LAYANAN INFORMASI UNTUK MENINGKATKAN PEMAHAMAN KARIER SISWA - Wardani, Silvia Yula; Trisnani, Rischa Pramudia (Universitas Muria Kudus, 2017)
The purpose of this study is to determine the effectiveness of information services to improve students' career understanding SMA Negeri 1 Wungu. This research was conducted in SMA Negeri 1 Wungu with pre-experimental design research design. Technique of collecting data using psychological scale that is scale of understanding of career. Data analysis technique using Wilcoxon Match Pairs Test. The result of the research shows that effective information service to improve interpersonal communication of high school students is proven after hypothetical test with Wilcoxon Signed Rank Test technique AsympSig (2-tailed) / asympiotic significance value 0.012, it can be concluded that information service to improve career understanding of SMA Negeri 1 Wungu students Regency of Madiun. It is suggested to improve the guidance and counseling service need to develop guidance and counseling service one of them is information service.